Republic of Congo : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper discusses reforms that could generate higher revenues from the non-oil sector through measures to rationalize the tax code, broaden the tax base, and increase administrative efficiency. These efforts should be complemented by economic diversification policies that support non-oil growth and thereby expand the potential tax base. The paper also reflects on lessons learned from other country experiences that could be relevant for the Republic of Congo. The authorities should step up revenue mobilization as a key component of their medium-term fiscal strategy. This will require a well-sequenced structure of reforms that includes three key elements. First, the newly created Tax Policy Unit in the Ministry of Finance should reduce institutional fragmentation and facilitate the design, coordination and implementation of a medium-term revenue strategy. Second, the government should urgently address the erosion of the tax base generated by an excessive and discretionary use of tax exemptions that do not comply with existing laws and regulations. Finally, the government should continue to focus on rationalizing the tax code, and increasing administrative efficiency to recover tax arrears, including through the modernization of existing income tax systems.